Seizure and unilateral facial nerve paralysis in a newborn with Dandy-Walker malformation – A case report - Bhakta, Subhajit; Pal, S; Chatterjee, A; Pan, A (Journal of College of Medical Sciences-Nepal, 2014)
The Dandy-Walker syndrome (DWS) is a rare posterior fossa malformation. It can have a varied presentation depending on the age. A newborn presenting with neonatal seizure along with unilateral facial nerve palsy is rather a rare presentation of DWS and very few such cases were reported in the past. We are reporting a case of a newborn male baby presenting with neonatal seizure within 48 hrs of birth along with right sided LMN type facial nerve palsy which on due course of investigation revealed as a case of Dandy–Walker malformation. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-1, 48-51 DOI: http://dx.doi.org/10.3126/jcmsn.v9i1.9673